Genome organization is a major component of gene expression control in response to stress and during the cell division cycle in trypanosomes. Issue 4 (April 2012) - Kelly, S.; Kramer, S.; Schwede, A.; Maini, P. K.; Gull, K.; Carrington, M.
Abstract : The trypanosome genome is characterized by RNA polymerase II-driven polycistronic transcription of protein-coding genes. Ten to hundreds of genes are co-transcribed from a single promoter; thus, selective regulation of individual genes via initiation is impossible. However, selective responses to external stimuli occur and post-transcriptional mechanisms are thought to account for all temporal gene expression patterns. We show that genes encoding mRNAs that are differentially regulated during the heat-shock response are selectively positioned in polycistronic transcription units; downregulated genes are close to transcription initiation sites and upregulated genes are distant. We demonstrate that the position of a reporter gene within a transcription unit is sufficient to reproduce this effect. Analysis of gene ontology annotations reveals that positional bias is not restricted to stress–response genes and that there is a genome-wide organization based on proximity to transcription initiation sites. Furthermore, we show that the relative abundance of mRNAs at different time points in the cell division cycle is dependent on the location of the corresponding genes to transcription initiation sites. This work provides evidence that the genome in trypanosomes is organized to facilitate co-coordinated temporal control of gene expression in the absence of selective promoters.